Safety issues and harmful pharmacological interactions of nutritional supplements in Duchenne muscular dystrophy: considerations for Standard of Care and emerging virus outbreaks. (August 2020) - Boccanegra, Brigida; Verhaart, Ingrid E.C.; Cappellari, Ornella; Vroom, Elizabeth; De Luca, Annamaria
Graphical abstract: Abstract: At the moment, little treatment options are available for Duchenne muscular dystrophy (DMD). The absence of the dystrophin protein leads to a complex cascade of pathogenic events in myofibres, including chronic inflammation and oxidative stress as well as altered metabolism. The attention towards dietary supplements in DMD is rapidly increasing, with the aim to counteract pathology-related alteration in nutrient intake, the consequences of catabolic distress or to enhance the immunological response of patients as nowadays for the COVID-19 pandemic emergency. By definition, supplements do not exert therapeutic actions, although a great confusion may arise in daily life by the improper distinction between supplements and therapeutic compounds. For most supplements, little research has been done and little evidence is available concerning their effects in DMD as well as their preventing actions against infections. Often these are not prescribed by clinicians and patients/caregivers do not discuss the use with their clinical team. Then, little is known about the real extent of supplement use in DMD patients. It is mistakenly assumed that, since compounds are of natural origin, if a supplement is not effective, it will also do no harm. However, supplements can have serious side effects and also have harmful interactions, in terms of reducing efficacy or leading to toxicity, with other therapies. It is therefore pivotal to shed light on this unclear scenario for the sake of patients. This review discusses the supplements mostly used by DMD patients, focusing on their potential toxicity, due to a variety of mechanisms including pharmacodynamic or pharmacokinetic interactions and contaminations, as well as on reports of adverse events. This overview underlines the need for caution in uncontrolled use of dietary supplements in fragile populations such as DMD patients. A culture of appropriate use has to be implemented between clinicians and patients' groups.